How Sex Ratio Influences the Population Dynamics of the Red Flour Beetle - Saunders, Jazmine; Marshall, Jeremy (My University, 2017)
Sex ratios can influence the population biology of organisms (Wade, M.j. 1984 and Lee, Smith 1978). Sex ratios can also influence the sexual and reproductive fitness of males and females (Michalczyk, ?ukasz 2011). I wanted to determine if manipulating the sex ratios would influence the sexual biology of red flour beetles. I tested this using three different male-female ratios and three replicates of each. I found out that the 2:1 malefemale ratio had an increased weight and fitness compared to the 1:1 and 5:1 ratios. This means that an increase in ratio will increase the reproductive fitness of red flours beetles to an extent; however, past the 2:1 ratio, it declines near the 1:1 ratio.
Citation: Saunders, J. (2017). How Sex Ratio Influences the Population Dynamics of the Red Flour Beetle . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.